Tricuspid Valve Incompetency Due to the Grenade Chip Embolization to the Heart. (June 2019) - Sarmast, Hossein; Takriti, Ahmad
Migration of foreign bodies into the heart, although unusual, has been reported since 1834 when Davis published the first bullet embolus. Our case was a 29-year-old woman who suffered from a grenade explosion wound with a residual burst fragment inside her arm soft tissue. Two months later, she was admitted with progressive fatigue, palpitation, shortness of breath, and swelling in legs and neck. She was taking hormonal therapy for infertility as medical history. Ascultation detected holosystolic respiratory variable murmur maximal over the left lower sternal border. Severe tricuspid regurgitation and an obliterating mass on tricuspid valve (TV) with characteristic of central linear echogenicity were detected by transthoracic echocardiography. The diagnosis of "the embolized missile into heart with superimposed thrombosis" was determined. The patient underwent open heart surgery and the thrombotic rod shape chip that was embedded in anterior tricuspid leaflet was removed and then TV was repaired.